Hodder Mathematics Intermediate; 2 - Catherine Berry (Hodder & Stoughton Educational, 2002)
Suitable for OCR's GCSE Mathematics Specification B (MEI; 1968), this work provides teaching material and practice questions with activities. It conveys the maths through real-life applications and contexts. At the end of each chapter, it offers a summary of key points and a mixed exercise.